Resurrecting Pragmatism as a Philosophical Frame for Understanding, Researching, and Developing Performance in the Small District Superintendency - Gary Ivory; Rhonda McClellan; Adrienne E. Hyle (Educational Considerations, 2009)
We propose in this article that pragmatism is a perspective with great promise for understanding and researching the work of small district superintendents and developing the abilities of both preservice students and in-service practitioners to do that work.
Keywords: Pragmatism; characteristics; performance; definitions; Superintendents; postmodernism; poststructuralism; postpositivism; Resurrecting